Supramolecular polymeric assembly of bimetallic gold (I) and silver (I) pyrazolate complexes for colour–tunable luminescent materials - Sabran, Nurul Husna (2015)
SabranDevelopment of metal complexes with tunable luminescent properties has received considerable attention due to the characteristic of their phosphorescent properties originating from polymeric assembly of a weak noncovalent metal–metal interaction for applications as sensor materials. Although luminescent properties of bimetallic gold(I) and silver(I) complexes in clusters compounds synthesized from silver salt in gold complexes have been studied for development of vapochromic sensors, there are no example of luminescent and their colour–tunable studies of these supramolecular polymeric complexes. Herein, we report the first study on luminescent changes of self–assembled trinuclear bimetallic gold(I) and silver(I) pyrazolate complexes using different side chains at pyrazole ring and molar ratios of gold(I) to silver(I) pyrazolate complexes. Both trinuclear gold(I) and silver(I) pyrazolate complexes (2[Au3Pz3]R and 3[Ag3Pz3]R) were successfully synthesized from the mixture of pyrazole ligands (1(PzH)R) having different side chains (R = H, CH3, and C6H5) with chloro(dimethylsulfide) gold(I) ([Au(SMe2)]Cl) and silver(I) hexafluorophosphate (AgPF6). Bimetallic pyrazolate complexes 4[Au3Pz3]@[Ag3Pz3]R were synthesized by mixing 2[Au3Pz3]R and 3[Ag3Pz3]R in dry dichloromethane for 1 hour with molar ratios of 1:1, 1:2, 1:3, 1:5, 1:10, 2:1, 3:1, 5:1, and 10:1. The resulting bimetallic 4[Au3Pz3]@[Ag3Pz3]H at molar ratio of 1:1 gave only one emission centered at 620 nm and shifted from 674 nm for 2[Au3Pz3]H and 459 nm for 3[Ag3Pz3]H when excited at 280 nm. Bimetallic 4[Au3Pz3]@[Ag3Pz3]CH3 also gave only one emission centered at 633 nm and shifted from 691 nm for 2[Au3Pz3]CH3 and 471 nm for 3[Ag3Pz3]CH3 when monitored at the same excitation wavelength. The emission peak of bimetallic 4[Au3Pz3]@[Ag3Pz3]H and 4[Au3Pz3]@[Ag3Pz3]CH3 were shifted from red to blue region when molar ratios of 3[Ag3Pz3]R to 2[Au3Pz3]R were increased with good agreement of changes in their emission centers. In contrast, when alkyl chain was C6H5, bimetallic complex 4[Au3Pz3]@[Ag3Pz3]C6H5 at the same molar ratio gave bright orange colour which consisted of two emission bands of gold complex at 624 nm and silver complex at 468 nm. When the molar ratios of 3[Au3Pz3]C6H5 were dominant, bimetallic complex 4[Au3Pz3]@[Ag3Pz3]C6H5 gave light purple colour where emission intensity at blue region was increased and red region was decreased. Compared to bimetallic complexes 4[Au3Pz3]@[Ag3Pz3]H and 4[Au3Pz3]@[Ag3Pz3]CH3, rigidity of side chains at pyrazole ring in the resulting bimetallic 4[Au3Pz3]@[Ag3Pz3]C6H5 suggests formation of different supramolecular assembly in the polymeric structure. The luminescent properties of bimetallic complexes 4[Au3Pz3]@[Ag3Pz3]R with different type of side chains at pyrazole ring and molar ratios will be discussed later in details.